The Work-ability Support Scale: Evaluation of Scoring Accuracy and Rater Reliability - Turner-Stokes, L; Fadyl, Joanna; Rose, H; Williams, H; Schlüter, P; McPherson, KM (Springer, 2014)
The Work-ability Support Scale (WSS) is a new tool designed to assess vocational ability and support needs following onset of acquired disability, to assist decision-making in vocational rehabilitation. In this article, we report an iterative process of development through evaluation of inter- and intra-rater reliability and scoring accuracy, using vignettes. The impact of different methodological approaches to analysis of reliability is highlighted.
Keywords: Rehabilitation; Vocational; Needs assessment; Reliability and validity